Bantuan Stimulan Perumahan Swadaya (BSPS) di Desa Pancar Jelobok Kecamatan Pintu Rime Gayo Kabupaten Bener Meriah: Masalah dan Solusi Bantuan Rumah Tidak Layak Huni (RTLH) Bagi Masyarakat Berpenghasilan Rendah (MBR) - Seri Mughni Sulubara; Riska Riska; Yeni Irma Normawati (Universitas 45 Surabaya, 2024)
Self-help Housing Stimulant Assistance (BSPS) is government assistance for low-income communities to encourage and increase self-help in improving the quality of houses and new construction of houses along with infrastructure, facilities, and public utilities. The problem in this research is that the people of Pancar Jelobok Village still only rely on BSPS program funds. It turns out that these funds are not enough for the construction or repair of their houses. So that the community actually has to try hard to find additional costs to increase costs outside of BSPS funding assistance in the form of self-help money, building materials and self-help labor sources. The purpose of this research is to find out the solution so that the BSPS program can be realized effectively, efficiently and sustainably in Pancar Jelobok Village.